Enhancing building energy system design using computational intelligence for smart buildings - Agrawal, Swati; Sahu, Madhu (Architecture Image Studies, 2025)
Building Energy (BE) use, representing around one-third of global energy usage, can be substantially diminished by implementing adaptable façades. This paper proposes a computational optimization method to improve the energy efficiency of buildings through the design of an adaptable façade structure capable of adjusting its thermal and visual transmittance in response to fluctuating climatic circumstances. The core of the adaptable façade design methodology is an automated optimizing procedure that integrates the BE simulation tool (Energy-Plus) with a strategy for optimization. This work utilizes a modified firefly method, an internal optimizing tool, to create an adaptable façade system. The suggested approach is not contingent upon any specific optimization tool and does not put limitations on the type of structure. The efficacy of the proposed strategy for improving BE usage is substantiated through two instances: a standard single office space and a medium-sized workplace. Compared to static facades, the suggested adaptable façade technology significantly decreases energy usage in both the first and second case studies. These notable results illustrate adaptable exteriors' capacity to improve structures' energy usage.